The time keeper [compact disc, unabridged] - Albom, Mitch, 1958- (Hyperion Audio, 2012)
After being punished for trying to measure God's greatest gift, Father Time returns to Earth along with a magical hourglass and a mission: a chance to redeem himself by teaching two earthly people the true meaning of time.